PELANGGARAN KODE ETIK POLISI REPUBLIK INDONESIA DALAM PENYIDIKAN TINDAK PIDANA PENCURIAN DENGAN KEKERASAN DI KEPOLISIAN RESOR SUMBA TIMUR - Radja Manu, Nikolas Bryan; Fallo, Debi F. Ng.; Kian, Darius Antonius (Petitum Law Journal, 2024)
This study aims to identify factors that cause violations of the code of ethics by members of the Indonesian National Police and to understand the application of the law to these violations at the East Sumba Police Resort. This study uses an empirical legal approach with a qualitative descriptive method. Data were collected through interviews with respondents who were directly related to the cases studied, as well as through document studies. The results of the study indicate that violations of the code of ethics in the investigation of violent theft crimes are caused by internal factors such as the subjective attitude of investigators who ignore the rights of suspects, as well as external factors such as lack of evidence and pressure from institutions to expedite the resolution of cases. In addition, violations also often occur because the perpetrators are recidivists, which makes police officers feel the need to provide a deterrent effect through violence. The application of the law to violations of this code of ethics has been regulated in the Regulation of the Head of the Indonesian National Police Number 7 of 2022 concerning the Police Professional Code of Ethics. However, even though the rules and sanctions have been established, violent practices by police officers still occur, reflecting the challenges in implementing the code of ethics. This study suggests the need for increased professional ethics training, stricter supervision, strict enforcement of sanctions, and strengthening transparency in the investigation process. These efforts are important to maintain the integrity and professionalism of the Police.